Laparoscopy of the genitourinary tract of small ruminants - Vrisman, D. P.; Choaire, E.; Strucher, F.; Oliveira, M. S.; Ribas, T. M B; Coutinho, L. N. [UNESP]; Mariano, R. S G [UNESP]; Oliveira, M. G.; Vicente, W. R R [UNESP]; Silva, M. A M; Teixeira, P. P M [UNESP] (My University, 2014)
Laparoscopic endosurgery is an important tool for small ruminant breeding especially due to its wide versatility, both in reproductive biotechnologies and therapeutic approach. The purpose of this review is to present the applicability and advantages of endosurgery for routine use in small ruminants. Several endosurgical techniques of the genitourinary tract of small ruminants, including artificial insemination, embryo transfer, and oocyte retrieval for IVF, ovariectomy, cystotomy and renal biopsy are approached. The endoscopic techniques can improve the development of potential zootechnical indexes on the short-term period in comparison to traditional approaches.
Keywords: Endosurgery treatment; Goats; Reproductive biotechnologies; Sheep